Saint Kitts and Nevis. Significant achievements 2010-2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Saint Kitts and Nevis are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as good agricultural practices, sustainability, marketing, business, Finance, leadership, greenhouse use, innovations, climate change resilience, agritourism, food security, and food safety and sanitation. Likewise, work was done on the use of water and soil, on the implementation of new methodologies and on pest control. Finally, assistance was provided to young people for their inclusion in agriculture.